Enhanced vection in older adults: Evidence for age-related effects in multisensory vection experiences. (October 2022) - Murovec, Brandy; Spaniol, Julia; Campos, Jennifer L.; Keshavarz, Behrang
The illusion of self-motion (vection) is a multisensory phenomenon elicited by visual, auditory, tactile, or other sensory cues. Aging is often associated with changes in sensory acuity, visual motion perception, and multisensory integration, processes which may influence vection perception. However, age-related differences in vection have received little study to date. Thus, the objective of the present study was to investigate age-related differences in vection during multisensory stimulation. Nineteen younger adults and 19 older adults were exposed to rotating visual, auditory, and tactile stimuli (separately or in combination) at a speed of 45°/s inside a VR laboratory inducing circular vection. The size of the field-of-view (FOV) was large (240°), medium (75°), small (30°), or contained no visuals. Vection intensity and duration were reported verbally after each trial. Overall, older adults experienced significantly stronger and longer vection compared to younger adults. Additionally, there were main effects of FOV and sensory cues, such that larger FOVs and the presence of auditory and tactile stimulation increased vection ratings for both age groups. These findings support the idea that vection is a multisensory experience that can be elicited by visual, auditory, and tactile stimuli and demonstrates these effects for the first time in older adults.